Long-Term Remission of Primary Bone Marrow Diffuse Large B-Cell Lymphoma Treated with High-Dose Chemotherapy Rescued by In Vivo Rituximab-Purged Autologous Stem Cells - Hiroshi Kazama; Masanao Teramura; Kentaro Yoshinaga; Akihiro Masuda; Toshiko Motoji (Case Reports in Medicine)
Primary bone marrow diffuse large B-cell lymphoma (DLBCL) is a rare type of extranodal lymphoma with poor prognosis. Here, we report a case of primary bone marrow DLBCL successfully treated with high-dose chemotherapy and rescued by in vivo rituximab-purged autologous stem cells. A 39-year-old woman visited our hospital because of anemia. Bone marrow examination revealed a large B-cell lymphoma invasion. An 18F-fluorodeoxyglucose positron emission tomography scan revealed disseminated bone marrow uptake without evidence of dissemination at other sites. These findings led to a diagnosis of primary bone marrow DLBCL. Our patient underwent R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) chemotherapy and achieved complete remission. Subsequently, she received high-dose chemotherapy with an in vivo rituximab-purged autologous stem cell transplant. Seven years have passed since the transplantation, and she remains in remission. This suggests that transplantation of an in vivo rituximab-purged autograft is a promising strategy for primary bone marrow DLBCL.